AB1365 Number needed to treat, cost per responder and budget impact of TNF inhibitors in the treatment of psoriatic arthritis. (23rd January 2014) - Ingham, M.; Ellis, L.; Bolge, S.
Abstract : Background: Lack of head to head data requires use of indirect comparison methods. National Institute for Health and Clinical Excellence (NICE) is a leader in comparative and cost effectiveness methodology. However, NICE's use of cost-effectiveness is UK focused and requires adaptation for consideration in the United States (U.S.). Objectives: To estimate the number needed to treat (NNT), cost per responder (CPR) and the U.S. budget impact (BI) of TNF inhibitors (TNFi) used in psoriatic arthritis (PsA), using clinical assumptions presented in an independent NICE systematic review. Methods: Comparative data were sourced from a February 2011 NICE systematic review and Bayesian indirect comparison of adalimumab (ADA), etanercept (ETA) and infliximab (IFX) in PsA, based on a systematic review of ten electronic databases and including published evidence of randomized controlled trials up to June 2009. Primary outcomes included Psoriatic Arthritis Response Criteria (PsARC) and Psoriasis Area and Severity Index (PASI) 75% response, plus American College of Rheumatology Improvement Criteria (ACR) 50% response and the Health Assessment Questionnaire (HAQ). NICE adjusted outcomes for each TNFi at 12 or 14 weeks vs a standardized placebo response, within each outcome, and these acute phase results were projected to 52 weeks for this analysis. All results represent percent responders, except HAQ which represents mean change from baseline. Biologic costs were estimated for this analysis from January 2012 Wholesale Acquisition Costs, using labeled dosing, over 52 weeks. NNT was calculated as inverse of differences in response rates. BI is based on costs over one year to treat 100 responders. Results: NICE reported results from six trials (two for each compound). Patient characteristics across trials were consistent and NICE reported quality of all trials as good. The authors of the independent NICE review concluded IFX appears to be the most effective of the three biologics, and stated that across all outcomes of joint and skin disease at 12 weeks, IFX is associated with the highest probabilities of response. The expected placebo-adjusted responses from the NICE report were as follows – PsARC: ADA (33.8%), ETA (46.4%), IFX (54.6%); PASI 75: ADA (43.4%), ETA (13.3%) and IFX (72.5%); ACR 50: ADA (26.2%), ETA (30.9%), IFX (38.0%) and HAQ: ADA (0.233), ETA (0.386) and IFX (0.413). Based on these data, this analysis derived that fifty-two week CPR was lowest for IFX for all outcomes. Also, for PASI 75, NNT to achieve 100 responders was 230.9, 751.9 and 137.9 for ADA, ETA and IFX respectively, with corresponding annual biologic costs to achieve 100 responders of $5.75M; $17.69M and $3.33M. Conclusions: In this analysis of projected 52 week relative outcomes and expected biologics costs, the incremental annual budget required to achieve 100 PASI 75 responders would be $2, 422, 816 or $14, 360, 355 greater if patients were initiated on ADA or ETA respectively, instead of IFX. Sensitivity analysis based on confidence intervals of response variables is warranted. References: Rodgers M, Epstein D, Bojke, L, Yang H, craig D, Fonseca T et al. Etanercept, infliximab and adalimumab for the treatment of psoriatic arthritis: a systematic review and economic evaluation. Health Technology Assessment (HTA) 2011, 15(10). www.hta.ac.uk Disclosure of Interest: M. Ingham Employee of: Janssen Scientific Affairs, LLC, L. Ellis Employee of: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC